2012
DOI: 10.2139/ssrn.2063557
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Governance Influence Convertible Bond Issuance?

Abstract: We examine the influence of corporate governance quality on firms' choice between convertible debt, straight debt, and equity using a Western European sample of security offerings made between 2000 and 2010. We find that weaker firm-specific and countryspecific corporate governance quality increases firms' likelihood of issuing convertible debt instead of straight debt and common equity. We also find that stockholder reactions to convertible debt announcements are more favorable for firms with weaker corporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 91 publications
3
10
0
2
Order By: Relevance
“…This result seems to be consistent with empirical findings by Isagawa () and Dutordoir et al. (), showing that convertibles alleviate firms' financial distress and are perceived as more valuable for firms with weaker corporate governance and higher distress costs. Furthermore, the gap between V cd and V sd widens as ambiguity aversion increases (see Figure ).…”
Section: The Modelsupporting
confidence: 92%
“…This result seems to be consistent with empirical findings by Isagawa () and Dutordoir et al. (), showing that convertibles alleviate firms' financial distress and are perceived as more valuable for firms with weaker corporate governance and higher distress costs. Furthermore, the gap between V cd and V sd widens as ambiguity aversion increases (see Figure ).…”
Section: The Modelsupporting
confidence: 92%
“…Similar to the findings in the US market, Dutordoir and Van de Gucht () and Dutordoir et al. () find quantitative evidence in favour of the RSH among Western European companies using stock return volatility to measure the cost of risk‐shifting. As qualitative evidence is garnered from analysing the surveys of CFOs, prior researchers have found that 72% of Western European CFOs consider convertibles to be less expensive than straight debts, which is consistent with the implications of the RSH.…”
Section: Discussionsupporting
confidence: 64%
“…With respect to control variables, the significantly negative coefficient of Net Income/Assets implies that profitable companies prefer straight debts because they experience no difficulties in paying interest (Dutordoir, Strong, & Ziegan, ; Lewis et al., ). The coefficients of Long‐term Debt/Assets , Volatility , and Slack are significantly positive.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our results based on the sample of public offerings support our heterogeneous belief explanation. The literature on the use of convertible securities also suggests an asymmetric information explanation: convertibles can help reduce adverse‐selection costs arising from information asymmetry (see, e.g., Brennan and Kraus ; Constantinides and Grundy ; Stein ; Chakraborty and Yilmaz ; Lewis, Rogalski, and Seward ; Finnerty, Jiao, and Yan ; Chemmanur et al forthcoming; Dutordoir, Strong, and Ziegan ).…”
Section: Introductionmentioning
confidence: 99%